Preparation and Characterization of Maleoylagarose/Pnipaam Graft Copolymers and Formation of Polyelectrolyte Complexes with Chitosan - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Ortiz-Nunez, J; Zapata-Ramirez, P (Elsevier Ltd, 2018)
A water soluble derivative in 98% yield with 23.1% incorporation of maleoyl groups was obtained by esterification of agarose with maleic anhydride. Graft copolymers were synthesized through vinyl groups of maleoylagarose with N-isopropylacrylamide using ceric ammonium nitrate or ammonium persulfate as initiator, by conventional method or microwave irradiation. High nitrogen content (4.6%) was obtained in the grafting process using ceric ammonium nitrate as initiator without microwave irradiation. Copolymers were characterized by FT-IR and NMR spectroscopies, TGA, DSC and morphological analysis by AFM and SEM microscopy, confirming the grafting of PNIPAAm onto polysaccharide backbone. Hydrogel films were obtained by ionic complexation between opposite charged groups of maleoylagarose-g-poly(N-isopropylacrylamide) and chitosan. The swelling of 1:1 w/v maleoylagarose-g-PNIPAAm:chitosan film was higher than 2:1 w/v film at 25 and 37 °C. 53% release in vitro of diclofenac sodium from 1:1 w/v maleoylagarose-g-PNIPAAm:chitosan was obtained at 37 °C and pH 6.0 with <0.5 diffusional constant values. © 2017 Elsevier Ltd